MicroRNA-186 promotes macrophage lipid accumulation and secretion of pro-inflammatory cytokines by targeting cystathionine γ-lyase in THP-1 macrophages. (July 2016) - Yao, Yan; Zhang, Xin; Chen, Hai-peng; Li, Liang; Xie, Wei; Lan, Gang; Zhao, Zhen-wang; Zheng, Xi-Long; Wang, Zong-bao; Tang, Chao-ke
Abstract: Background and aims: Several studies suggest that cardiomyocyte-enriched miR-186 is involved in cardiac injury and myocardial infarction, and also plays an important role in atherosclerotic diseases, but the underlying mechanism is unknown. Cystathionine-γ-lyase (CSE) is the predominant enzyme to produce H2 S in the cardiovascular system. Here, miR-186 was identified to bind to the 3′UTR of CSE. In this study, we aimed at exploring whether miR-186 affects lipid accumulation and secretion of pro-inflammatory cytokines by targeting CSE and its underlying mechanism in human THP-1 macrophages and peripheral blood monocyte-derived macrophages (PBMDM). PBMDM just as a control group for the comparison with the THP-1 macrophages. Methods: MiR-186 target genes, CSE 3′UTR sequence and free energy were predicted and analyzed by bioinformatics analyses and dual-luciferase reporter assays. The expression of CSE mRNA and protein were measured by real-time quantitative PCR and western blot analyses. The lipid accumulation in THP-1 macrophages was detected by high performance liquid chromatography (HPLC). The effects of miR-186 on secretion of IL-6, IL-1β and TNF-α were examined by ELISA. Endogenous H2 S was detected by spectrophotometry. Using small interfering RNA (siRNA) approach to decrease the expression of CSE protein and mRNA. Results: We found that miR-186 directly inhibited CSE protein and mRNA expression through targeting CSE 3′UTR by bioinformatics analyses and dual-luciferase reporter assays. HPLC assays showed that miR-186 increased the lipid accumulation in human THP-1 macrophages. We also showed that miR-186 enhanced secretion of pro-inflammatory cytokines in human THP-1 macrophages. Using siRNA approach, we found that CSE siRNA could inhibit the miR-186 inhibitor-induced decrease in the expression of LPL protein and mRNA in human THP-1 macrophages, which was accompanied a decrease in the level of H2 S. Conclusions: MicroRNA-186 promotes macrophage lipid accumulation and pro-inflammatory cytokine secretion by targeting cystathionine γ-lyase in THP-1 macrophages. Highlights: MiR-186 suppresses the expression of CSE directly by binding on CSE 3′UTR, and then endogenous H2 S production is decreased. Decreased production of endogenous H2 S contribute to increased expression of LPL. Overexpression LPL promote pro-inflammatory cytokine secretion and cellular lipid accumulation.